FAKTOR INTERNAL PENDUKUNG KEMAMPUAN BERBICARA BAHASA INGGRIS PESERTA DIDIK KELAS IV: STUDI KUALITATIF DI SDN PONDOK KELAPA 05 JAKARTA - Amelia, Sisca; Otib Satibi Hidayat (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research aims to describe the internal factors that support grade IV students' mastery of English speaking skills. The subjects in this research were three students in class IV-B at SDN Pondok Kelapa 05 Jakarta. The method used is a descriptive method with a qualitative approach. Data collection was carried out using observation, interviews and documentation techniques. The research results found that there are seven supporting factors that influence the ability to speak English, namely discipline and readiness to learn, intrinsic motivation, social awareness, self-confidence, personality quality, ability to collaborate and social interaction, and strategies for overcoming challenges.